Critter jokes & riddles - Myers, Janet Nuzum; Clegg, Dave (New York : Sterling, 2007)
This is a collection of jokes and riddles that feature almost every creature that walks, hops, flies, swims, or slithers.
Includes index.
K-3
Keywords: Animals -- Humor; Riddles